Method for catalyzing and degrading waste plastic through light / sound concerted catalysis and upgrading and converting of waste plastic to promote acquisition of clean fuel

By using a photo/acoustic synergistic catalysis method, MTSJA supported catalysts were used to degrade waste plastics, solving the problem of traditional photocatalysis relying on sunlight. This achieved efficient degradation and clean fuel generation, promoting the resource utilization of waste plastics.

CN120829786APending Publication Date: 2025-10-24WUHAN TEXTILE UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202410474674.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-04-19
Publication Date
2025-10-24

AI Technical Summary

Technical Problem

Traditional photocatalytic degradation of plastics relies on sunlight, but its efficiency is greatly reduced in water bodies rich in microplastics or in environments with insufficient sunlight, and it also wastes resources significantly, requiring additional sacrificial agents and increasing economic costs.

Method used

A photo/acoustic synergistic catalytic method was adopted to prepare an MTSJA supported catalyst using g-C3N4, cadmium acetate and thioacetamide. The catalyst was then loaded onto aerogel, hydrogel or non-woven fabric and combined with xenon lamp irradiation and ultrasonic treatment of waste plastics to promote free radical formation and catalytic degradation.

Benefits of technology

It enables the efficient degradation of waste plastics to generate clean fuels such as methane without energy consumption or the generation of toxic gases, thus solving the plastic pollution problem and providing a solution for obtaining clean energy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120829786A_ABST
    Figure CN120829786A_ABST
Patent Text Reader

Abstract

The invention provides a method for promoting acquisition of clean fuel by light / sound concerted catalytic degradation of waste plastics and upgrading and conversion thereof, which comprises the following steps: uniformly mixing g-C3N4, cadmium acetate and thioacetamide according to a predetermined proportion, pouring into a reaction kettle, placing in a high-temperature oven for a predetermined time, centrifuging, cleaning and drying to obtain a catalyst, the method comprises the following steps: loading a catalyst on the surface of aerogel, hydrogel or non-woven fabric to obtain an MTSJA-loaded catalyst, treating waste plastic with NaOH, adding the MTSJA-loaded catalyst, stirring under irradiation of a xenon lamp, starting ultrasound for reaction, and carrying out light / sound synergistic catalytic degradation on the waste plastic. According to the method, energy consumption is not needed, toxic and harmful gas is not generated, the purposes of energy conservation and environmental protection can be achieved, meanwhile, carbon dioxide in water can be catalytically reduced to generate clean energy such as methane in the process of degrading the waste plastic, and further obtaining of the energy is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of plastic degradation, and particularly relates to a method for degrading waste plastics by light / sound synergistic catalysis and upgrading conversion to promote clean fuel acquisition. BACKGROUND

[0002] Plastics are mainly formed by carbon and hydrogen through polymerization, which are not only closely related to our daily life, but also widely used in industry. While the demand for plastics is increasing, it also causes the accumulation of solid waste. Waste plastics take several centuries to degrade in nature. Due to the erosion and aging of plastics, they are broken and cracked into microplastic particles, which enter the human body through the food chain or drinking water and accumulate, thereby seriously threatening public health.

[0003] Waste plastics are expected to be resourceized through upgrading and recycling processes. For example, waste plastics can be used as a photocatalytic sacrificial agent to absorb holes to promote the reduction of water, carbon dioxide and nitrogen dioxide. Traditional photocatalytic degradation of plastics requires the addition of additional sacrificial agents such as triethanolamine and methanol, which not only wastes resources but also increases economic costs. Photocatalytic technology can convert plastic waste into fuel and high-value chemicals through photocatalytic redox reactions. However, photocatalysis is heavily dependent on sunlight, and once it enters water bodies rich in microplastics or encounters environments with insufficient sunlight, the degradation efficiency will be greatly reduced.

[0004] Ultrasonic waves have good directivity and strong penetration. If they are applied to photocatalysis, they have great advantages and can synergistically promote photocatalysis. Local tensile stress occurs in the liquid to form negative pressure, and the reduction of pressure makes the gas originally dissolved in the liquid supersaturated, and escapes from the liquid to become small bubbles. The internal friction accompanying cavitation can form charges and produce light emission in the bubbles due to discharge, thereby producing "sonoluminescence" and local high temperature and high pressure (5000K, 1800atm). The ultrasonic field can induce internal piezoelectric potential in sonosensitizing materials (such as C3N4 and CdS), thereby promoting the formation of free radicals. The use of ultrasonic waves in conjunction with photocatalysis can separate water to produce hydroxyl radicals and the like, reduce the recombination of carriers, and further promote the degradation effect of photocatalysis.

[0005] Therefore, it is necessary to design an improved method for degrading waste plastics by light / sound synergistic catalysis and upgrading conversion to promote clean fuel acquisition to solve the above problems. SUMMARY

[0006] In view of the defects of the prior art, the present application aims to provide a method for degrading waste plastics and upgrading conversion of waste plastics to promote clean fuel acquisition by using light / sound synergy, which uses plastics as substrates, does not consume energy and does not produce toxic gases, achieves the purpose of energy saving and environmental protection, and is environmentally friendly.

[0007] To achieve the above-mentioned purpose, the present application provides a method for degrading waste plastics and upgrading conversion of waste plastics to promote clean fuel acquisition by using light / sound synergy, which comprises the following steps:

[0008] S1, annealing thiourea or urea in a muffle furnace to obtain g-C3N4, mixing g-C3N4, cadmium acetate and thioacetamide according to a predetermined ratio, adding deionized water, ultrasonic mixing until uniform, pouring into a reaction kettle, placing in a high-temperature oven for a predetermined time, taking out, centrifuging, cleaning with deionized water and ethanol, and drying to obtain a catalyst;

[0009] S2, mixing ethanol and deionized water according to a predetermined ratio, adding the catalyst obtained in step S1, ultrasonic mixing until uniform, smearing the mixture on the surface of a carrier, and drying in an oven to obtain an MTSJA loaded catalyst;

[0010] S3, washing and drying waste plastics, soaking the plastic fragments in NaOH for a predetermined time to obtain a mixture;

[0011] S4, adding the MTSJA loaded catalyst obtained in step S2 to the mixture obtained in step S3, stirring under xenon lamp irradiation, and simultaneously starting ultrasonic reaction;

[0012] S5, after the reaction stops, separating the residue and the liquid and storing them respectively.

[0013] As a further improvement of the present application, in step S1, the mass ratio of g-C3N4, cadmium acetate and thioacetamide is (80-100):4:2, the temperature of the high-temperature oven is 120-200℃, and the predetermined time is 4-8h.

[0014] As a further improvement of the present application, in step S2, the volume ratio of ethanol to deionized water is (1-7):10, the mass ratio of the carrier to the catalyst is (10-20):1, and the drying temperature is 30-60℃.

[0015] Further, the carrier is one of aerogel, hydrogel or non-woven fabric.

[0016] As a further improvement of the present invention, in step S3, the amount of the plastic fragments is 0.1-0.2 g, the concentration of NaOH is 5-10 mol / L, and the amount is 10-20 ml; the soaking temperature is 20-50° C., and the predetermined time is 12-24 h.

[0017] As a further improvement of the present invention, the mass ratio of the waste plastic to the catalyst is (10-30):(2-5).

[0018] As a further improvement of the present invention, in step S4, the power of the xenon lamp is 200-400W, the filter wavelength of the xenon lamp is 350-450nm; the power of the ultrasound is 10-100W; and the reaction time is 6-12h.

[0019] The beneficial effects of the present invention are:

[0020] (1) The present invention provides a method for photo-acoustic synergistic catalytic degradation of waste plastics and their upgrading and conversion to promote the acquisition of clean fuels. The method comprises the following steps: preparing a catalyst by mixing g-C3N4, cadmium acetate and thioacetamide; loading the catalyst on the surface of aerogel, hydrogel or non-woven fabric to obtain an MTSJA-loaded catalyst; soaking the waste plastics in NaOH and then adding the MTSJA-loaded catalyst; stirring the mixture under xenon lamp irradiation; and simultaneously turning on ultrasound to react. The method does not require energy consumption and does not produce toxic and harmful gases, thereby achieving the purpose of energy conservation and environmental protection. In addition, the method can catalytically reduce carbon dioxide in water to generate clean energy such as methane during the degradation of the waste plastics, thereby promoting further energy acquisition.

[0021] (2) Carbon dioxide is difficult to convert in water because many photosensitizers or catalysts will degrade in water, so the efficiency is very low. The MTSJA-loaded catalyst of the present invention can simultaneously utilize light and sound. Compared with ordinary photocatalysts or sound catalysts, it achieves light / sound synergy and promotes the upgrading and conversion of waste plastics.

[0022] (3) Ultrasonic fields can promote the catalytic activity of photocatalysis, improve the efficiency of photocatalysis, make up for the dependence of photocatalysis on sunlight intensity, solve the long-standing problem of plastic pollution, especially marine plastic pollution, realize the value-added recycling of waste plastics, and provide ideas for obtaining clean energy in the context of energy crisis. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 These are SEM images of PET before and after degradation in Example 1 of the present invention.

[0024] Figure 2 These are SEM images of PET folded in half before and after degradation in Example 1 of the present invention.

[0025] Figure 3The mass loss statistical graph of PET in the present embodiment 1 and the comparative examples 1-2.

[0026] Figure 4 The infrared spectrum graph of PET in the present embodiment 1 and the comparative examples 1-2.

[0027] Figure 5 The DSC graph of PET in the present embodiment 1 and the comparative examples 1-2.

[0028] Figure 6 The production rate graph of CO in the present embodiment 1 and the comparative examples 1-2.

[0029] Figure 7 The production rate graph of CH4 in the present embodiment 1 and the comparative examples 1-2.

[0030] Figure 8 The production rate graph of H2 in the present embodiment 1 and the comparative examples 1-2.

[0031] Figure 9 The production rate graph of H2, CO and CH4 in the present embodiment 1 and the comparative example 3. DETAILED DESCRIPTION

[0032] In order to make the objects, technical solutions and advantages of the present application clearer, the present application will be described in detail below with reference to the drawings and specific embodiments.

[0033] Here, it also needs to be explained that, in order to avoid the present application being obscured by unnecessary details, only the structures and / or processing steps closely related to the scheme of the present application are shown in the drawings, and other details not closely related to the present application are omitted.

[0034] In addition, it also needs to be explained that the term “comprise”, “include” or any other variant thereof is intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements not only includes those elements, but also includes other elements not explicitly listed or inherent to such process, method, article or equipment.

[0035] The present application provides a method for synergistically catalytic degradation of waste plastics by light / sound and upgrading conversion to promote clean fuel acquisition, comprising the following steps:

[0036] S1, annealing thiourea or urea in a muffle furnace to obtain g-C3N4, mixing g-C3N4, cadmium acetate and thioacetamide, adding deionized water, ultrasonic mixing until uniform, pouring into a reaction kettle, placing in a high-temperature oven for a predetermined time, taking out and centrifuging, washing with deionized water and ethanol, and drying to obtain a catalyst.

[0037] Specifically, thiourea or urea is annealed in a muffle furnace to obtain g-C3N4, g-C3N4, cadmium acetate and thioacetamide are mixed in a ratio of (80-100):4:2, deionized water is added in an appropriate amount, ultrasonic mixing is performed until the mixture is uniform, the mixture is poured into a reaction kettle, and the mixture is placed in a high-temperature oven for a predetermined time. After being taken out, centrifuged, washed with deionized water and ethanol, and dried, a catalyst is obtained.

[0038] In the above step, the temperature of the high-temperature oven is 120-200℃, and the predetermined time is 4-8h.

[0039] S2, ethanol and deionized water are mixed in a certain ratio, the catalyst obtained in step S1 is added, ultrasonic mixing is performed until the mixture is uniform, the mixture is applied to the surface of the carrier, and the mixture is placed in an oven for drying to obtain an MTSJA loaded catalyst.

[0040] In the above step, the volume ratio of ethanol to deionized water is (1-7):10, the mass ratio of the carrier to the catalyst is (10-20):1, and the drying temperature is 30-60℃. The carrier is one of aerogel, hydrogel or non-woven fabric. Preferably, the carrier is a hydrophilic aerogel prepared from nanofibers. In this way, the catalyst can be uniformly dispersed in the solution to form a turbid solution, which is applied to the surface of the aerogel, dried and shaped. During this process, the catalyst will be captured and embedded in the pores of the nanofiber hydrophilic aerogel, and firmly adhered to the surface of the aerogel. This can make the catalyst better dispersed on the carrier, increase the contact area of the catalyst, and enhance the stability, activity and selectivity of the catalyst, thereby improving the efficiency of the catalytic reaction.

[0041] S3, the waste plastic is washed, dried and cut into pieces, and the plastic pieces are soaked in NaOH for a predetermined time to obtain a mixed solution.

[0042] Specifically, the amount of plastic pieces is 0.1-0.2g, and the plastic pieces are soaked in NaOH at 20-50℃ for 12-24h to obtain a mixed solution.

[0043] In the above step, the concentration of NaOH is 5-10mol / L, and the amount of NaOH is 10-20ml.

[0044] S4, the MTSJA loaded catalyst obtained in step S2 is added to the mixed solution obtained in step S3, and stirring is performed under xenon lamp irradiation, while ultrasonic reaction is performed.

[0045] Specifically, the mass ratio of waste plastics to the catalyst obtained in step S1 is (10-30):(2-5), stirring under xenon lamp irradiation, and placing an ultrasonic probe to turn on the ultrasonic wave, or placing in an ultrasonic machine for reaction, the power of the ultrasonic wave is 10-100 W. The MTSJA loaded catalyst is in full contact with the plastics, and the reaction is carried out for 6-12 h. In this way, the amount of catalyst is sufficient to fully catalyze the cracking reaction, while avoiding the generation of too much byproduct and waste; under the irradiation of the xenon lamp, the plastics and the catalyst in the reaction system can absorb the light and react, improving the activity of the catalyst; the vibration of the ultrasonic wave further accelerates the activation of the catalyst, promotes the catalyst to better penetrate into the plastics and achieve effective degradation, and through the action of the ultrasonic wave, the reaction surface area of the waste plastics is increased, and the contact area between the catalyst and the waste plastics is also expanded. The light / sound cooperation accelerates the reaction rate, promotes the full contact of the waste plastics with the catalyst, and improves the reaction efficiency and catalytic activity.

[0046] In the above step, the power of the xenon lamp is 200-400 W, preferably 300 W, in this way, sufficient spectral radiation can smoothly enter the reaction system to produce a reaction, while avoiding excessive heating of the reaction system caused by too high power; the wavelength of the filter of the xenon lamp is 350-450 nm, preferably 420 nm, in this way, the catalytic effect of the MTSJA loaded catalyst in the reaction system can be enhanced, and the reaction efficiency can be improved.

[0047] S5, after the reaction is stopped, the residue and the liquid are separated and stored respectively.

[0048] The method for light / sound cooperative catalytic degradation of waste plastics and upgrading conversion to promote clean fuel acquisition provided by the application will be described below in combination with specific examples.

[0049] Example 1

[0050] Example 1 provides a method for light / sound cooperative catalytic degradation of waste plastics and upgrading conversion to promote clean fuel acquisition, which comprises the following steps:

[0051] S1, urea is annealed in a muffle furnace to obtain g-C3N4, g-C3N4, cadmium acetate and thioacetamide are mixed in a mass ratio of 80:4:2, a proper amount of deionized water is added, and ultrasonic is applied until the mixture is uniform, then the mixture is poured into a reaction kettle, and placed in a high-temperature oven at 120℃ for 8 h, then taken out, centrifuged, cleaned with deionized water and ethanol, and dried to obtain a catalyst;

[0052] S2, ethanol and deionized water are mixed in a ratio of 1:10, 20 mg of the catalyst is added, and ultrasonic is applied until the mixture is uniform, then the mixture is applied on the surface of a common hydrophilic nanofiber aerogel, and placed in an oven for drying to obtain a MTSJA loaded catalyst;

[0053] S3, the waste plastic bottle (material is PET) is cleaned, dried, cut, 0.1g plastic pieces are soaked in 10ml NaOH with a concentration of 5mol / L at 30℃ for 12h, and a mixed solution is obtained;

[0054] S4, the mixed solution obtained in step S2 is added with MTSJA loaded catalyst, a 300W xenon lamp is used as a visible light source, a filter with a wavelength of 420nm is used for irradiation, ultrasonic is started at the same time, the power of the ultrasonic is 50W, and the reaction is carried out for 8h;

[0055] S5, after the reaction is stopped, the plastic piece residue is separated from the liquid, and the liquid is detected by high performance liquid chromatography, it is found that the plastic is degraded to generate many small molecules, including formic acid, ethylene glycol and glyoxal.

[0056] The SEM diagrams of PET before and after degradation in example 1 are as shown in Figure 1 It can be seen from the diagram that the surface of the original PET film is smooth, and the surface of the PET film after light / sound degradation is rough and many chippings appear; the SEM diagrams of PET before and after degradation in example 1 are as shown in Figure 2 It can be seen from the diagram that the surface of the original PET film is almost free of cracks after being folded, and the surface of the PET film after light / sound treatment appears serious cracks after being folded.

[0057] Example 2

[0058] Example 2 provides a method for degrading waste plastics and promoting clean fuel acquisition through upgrading and conversion by light / sound synergistic catalysis, comprising the following steps:

[0059] S1, g-C3N4 is obtained by annealing urea in a muffle furnace, g-C3N4, cadmium acetate and thioacetamide are mixed in a mass ratio of 90:4:2, appropriate deionized water is added, and ultrasonic is used until the mixture is uniform, then the mixture is poured into a reaction kettle, placed in a high temperature oven at 160℃ for 6h, taken out, centrifuged, cleaned with deionized water and ethanol, and dried to obtain a catalyst;

[0060] S2, ethanol and deionized water are mixed in a ratio of 4:10, 30mg of catalyst is added, ultrasonic is used until the mixture is uniform, the mixture is applied on the surface of ordinary hydrophilic nanofiber aerogel, and the mixture is placed in an oven to dry, to obtain MTSJA loaded catalyst;

[0061] S3, the waste plastic bottle (material is PET) is cleaned, dried, cut, 0.2g plastic pieces are soaked in 15ml NaOH with a concentration of 10mol / L at 20℃ for 15h, and a mixed solution is obtained;

[0062] S4, the mixed solution obtained in step S2 is added with the MTSJA loaded catalyst, a 300W xenon lamp is used as a visible light source, irradiation is performed with a filter having a wavelength of 420nm, and meanwhile, ultrasonic is turned on for reaction, the power of the ultrasonic is 10W, and the reaction is performed for 12h;

[0063] S5, after the reaction is stopped, the plastic piece residue and the liquid are separated and stored respectively.

[0064] Example 3

[0065] The method provided in Example 1 is a method for synergistically catalyzing degradation of waste plastics by light / sound and promoting upgrading conversion of the waste plastics to obtain clean fuel, and the method comprises the following steps:

[0066] S1, g-C3N4 is obtained by annealing urea in a muffle furnace, g-C3N4, cadmium acetate and thioacetamide are mixed according to a mass ratio of 100:4:2, appropriate deionized water is added, ultrasonic is performed until the mixture is uniform, the mixture is poured into a reaction kettle, and the reaction kettle is placed in a high-temperature oven at 200℃ for 4h, then the reaction kettle is taken out, centrifuged, cleaned with deionized water and ethanol, and dried to obtain a catalyst;

[0067] S2, ethanol and deionized water are mixed according to a ratio of 7:10, 50mg of the catalyst is added, ultrasonic is performed until the mixture is uniform, the mixture is applied to the surface of a common hydrophilic nanofiber aerogel, and the mixture is dried in an oven to obtain a MTSJA loaded catalyst;

[0068] S3, a waste plastic bottle (made of PET) is cleaned, dried and cut into pieces, 0.3g of the plastic pieces is soaked in 20ml of NaOH with a concentration of 8mol / L at 50℃ for 12h to obtain a mixed solution;

[0069] S4, the MTSJA loaded catalyst is added to the mixed solution obtained in step S2, a 300W xenon lamp is used as a visible light source, irradiation is performed with a filter having a wavelength of 420nm, and meanwhile, ultrasonic is turned on for reaction, the power of the ultrasonic is 100W, and the reaction is performed for 6h;

[0070] S5, after the reaction is stopped, the plastic piece residue and the liquid are separated and stored respectively.

[0071] Comparative Examples 1-2

[0072] Comparative Examples 1-2 respectively provide a method for synergistically catalyzing degradation of waste plastics by light / sound and promoting upgrading conversion of the waste plastics to obtain clean fuel, and compared with Example 1, the difference is that, in Comparative Example 1, the ultrasonic is not turned on, and the MTSJA loaded catalyst is used for reaction alone; in Comparative Example 2, the MTSJA loaded catalyst is not added, and the ultrasonic is used for reaction alone; other experimental parameters and conditions are basically the same as those of Example 1, and will not be described herein.

[0073] The mass loss of PET in Example 1 and Comparative Examples 1-2 is as followsFigure 3 As shown, the weight loss of PET is significantly increased to 29.3% by using the method for degrading waste plastics by light / sound synergistic catalysis, compared with the weight loss of 24.1% and 27.7% by sound catalytic degradation and photocatalytic degradation respectively; the infrared spectrum of PET is as shown in Figure 4 As shown, after different degradation treatments, the intensity of all peaks of PET decreases, accompanied by some displacement of individual peaks, for example, the C-H stretching vibration is displaced from 2920 cm -1 to 2966 cm -1 , which is related to the essential change of the internal molecular structure after degradation; the DSC graph is as shown in Figure 5 As can be seen from the thermal information read from the DSC characterization, the crystallinity of the degraded PET film slightly increases, and the increase of the crystallinity of PET proves the preferential attack of active species on the amorphous state, the weakening of intermolecular forces, the decrease of crystallinity, which means that the internal molecular chain arrangement of PET becomes disordered, the intermolecular forces are weakened, and the attack of active species is also facilitated.

[0074] The production rates of CO, CH4 and H2 in Example 1 and Comparative Examples 1-2 are as shown in Figures 6-8 As can be seen, by using the method for degrading waste plastics by light / sound synergistic catalysis of the present application, the highest CO production rate is 64.3 μmol·g -1 , which is 1.47 times and 5.9 times that of photocatalysis and sound catalysis respectively. The light / sound synergistic catalysis can achieve a H2 production value of 97.9 μmol·g -1 , compared with ordinary photocatalysts or sound catalysts, the method of the present application can significantly improve the production rates of CO, CH4 and H2.

[0075] Comparative Example 3

[0076] Comparative Example 3 provides a method for degrading waste plastics by light / sound synergistic catalysis and promoting clean fuel acquisition by upgrading conversion, which is different from Example 1 only in that the catalyst obtained in step S1 is directly added to the mixed solution obtained in step S3 for light / sound synergistic catalytic reaction, and other experimental parameters and conditions are basically the same as those of Example 1, which will not be described here.

[0077] Figure 9 The H2, CO and CH4 production rate graphs in Example 1 and Comparative Example 3 of the present application are as shown in the figure, from which it can be seen that the use of MTSJA loaded catalyst can significantly improve the production rates of H2, CO and CH4, and the catalyst loaded on aerogel can increase the dispersity, stability and catalytic performance of the catalyst compared with ordinary catalysts, and is convenient for recycling and reuse.

[0078] In summary, the method for degrading waste plastics and upgrading conversion to promote clean fuel provided by the application cooperatively catalyzes the degradation of waste plastics by light / sound, improves the efficiency compared with pure photocatalysis or sonocatalysis, and promotes the generation of clean energy during the degradation process. In the environment crisis of serious waste plastic pollution, clean fuel can be obtained by taking plastics as a substrate, realizing the recycling of energy utilization, and achieving the acquisition of clean energy without adding other sacrificial agents.

[0079] The above examples are only used to illustrate the technical solutions of the application but not limit the application. Although the application has been described in detail with reference to the preferred embodiments, it will be understood by those skilled in the art that the technical solutions of the application can be modified or replaced equivalently without departing from the spirit and scope of the technical solutions of the application.

Claims

1. A method for synergistically photocatalytic degradation of waste plastics and upgrading conversion to promote clean fuel acquisition, characterized in that, The method comprises the following steps: S1, annealing thiourea or urea in a muffle furnace to obtain g-C3N4, mixing g-C3N4, cadmium acetate and thioacetamide according to a predetermined proportion, adding deionized water, ultrasonic mixing until uniform, pouring into a reaction kettle, placing in a high-temperature oven for a predetermined time, taking out, centrifuging, cleaning with deionized water and ethanol, and drying to obtain a catalyst; S2, mixing ethanol and deionized water according to a predetermined proportion, adding the catalyst obtained in step S1, ultrasonic mixing until uniform, smearing the mixed solution on the surface of a carrier, and placing in an oven for drying to obtain an MTSJA loaded catalyst; S3, cleaning and air-drying waste plastics, cutting the waste plastics into pieces, soaking the plastic pieces in NaOH for a predetermined time to obtain a mixed solution; S4, adding the MTSJA loaded catalyst obtained in step S2 to the mixed solution obtained in step S3, stirring under xenon lamp irradiation, and simultaneously performing ultrasonic reaction; S5, after the reaction stops, separating the residue and the liquid and storing them respectively.

2. The method for synergistically photocatalytic degradation of waste plastics and upgrading conversion to obtain clean fuel according to claim 1, characterized in that, In step S1, the mass ratio of g-C3N4, cadmium acetate and thioacetamide is (80-100):4:

2.

3. The method for synergistically catalytic degradation of waste plastics and upgrading conversion to obtain clean fuel according to claim 1, characterized in that, In step S1, the temperature of the high-temperature oven is 120-200℃, and the predetermined time is 4-8h.

4. The method for synergistically photocatalytic degradation of waste plastics and upgrading conversion to clean fuel according to claim 1, characterized in that, In step S2, the volume ratio of ethanol to deionized water is (1-7):10, the mass ratio of the carrier to the catalyst is (10-20):1, and the drying temperature is 30-60℃.

5. The method for synergistically photocatalytic degradation of waste plastics and upgrading conversion to clean fuel according to claim 4, characterized in that, The carrier is one of aerogel, hydrogel or non-woven fabric.

6. The method for synergistically photocatalytic degradation of waste plastics and upgrading conversion to clean fuel according to claim 1, characterized in that, In step S3, the amount of plastic pieces is 0.1-0.2g, the concentration of NaOH is 5-10mol / L, and the amount of NaOH is 10-20ml.

7. The method for synergistically photocatalytic degradation of waste plastics and upgrading conversion to clean fuel according to claim 1, characterized in that, In step S3, the soaking temperature is 20-50℃, and the predetermined time is 12-24h.

8. The method for synergistically photocatalytic degradation of waste plastics and upgrading conversion to clean fuel according to claim 1, characterized in that, The mass ratio of the waste plastics to the catalyst is (10-30):(2-5).

9. The method for synergistically photocatalytic degradation of waste plastics and upgrading conversion to clean fuel according to claim 1, characterized in that, In step S4, the power of the xenon lamp is 200-400W, and the wavelength of the filter is 350-450nm.

10. The method for synergistically photocatalytic degradation of waste plastics and upgrading conversion to clean fuel according to claim 1, characterized in that, In step S4, the power of the ultrasonic is 10-100W, and the reaction time is 6-12h.

Citation Information

Cited By

  • Anaerobic sludge-g-C3N4 composite material as well as preparation method and application thereof

    CN121623830A

  • An anaerobic sludge-g-C3N4 composite material, its preparation method and application

    CN121623830B